Escherichia coli (e.coli) distribution and persistence in water and sediment at batang ai reservoir, Sarawak - Nurulhanis, Ahmad Sanusi (Universiti Malaysia Sarawak, UNIMAS, 2010)
Fecal coliforms are indicator organisms used worldwide to monitor water quality. Escherichia coli (E. coli) was chosen as the test organisms because of its acceptance as an indicator of fecal pollution. The study of populations of Escherichia coli (E. coli) in water and sediment sample were conducted from October 2009 to February 2010 at five sampling sites which were residential area, control with no visible human activities, hotel, fish cage culture, and shops and jetty. The mean population of E. coli in water sample was highest in shops and jetty site due to inefficient management of sewage from the shops and the facilities such as the toilet as well as from the boat landed area. Meanwhile, the E. coli population in sediment sample was highest in control site. In survival study of E. coli, it was observed that E. coli survived longer in sterile sediment compared to non-sterile sediment. This was possibly because of the removal of the pressure on survival induced by the competition with predators such as protozoan and viruses. In addition, the survival of E. coli in sediment was also affected by the organic matter content and particle size. Fine clay particle and high organic matter content in control site contributed to high E. coli population and survive longer almost 2 weeks in sediment. E. coli cannot survive longer in sediment at shops and jetty sites due to high percent of clay content which created greater water stress. Besides that, E. coli can grow and survive better at temperature of 25˚C compared to 30˚C.